عقد الإجارة ثم البيع كما تجريه المؤسسات المصرفية في ماليزيا: دراسة نقدية = 'Aqd al-ijarah summa al-bay' kama tajribah al-muassasah al-masrifiyyah fi Malizia: dirasah naqdiyyah - Mat Jubri@Shamsuddin, Mustafa (2012)
This research studies an Islamic financial contract which named as Leasing followed by Selling (al-Ijarah Thumma al- Bay’). This study consists of an introduction, two chapters and a conclusion. In the first chapter the researcher points to conceptual meanings of some terms related to the topic. In the second chapter the researcher highlights application of the contract in Malaysian financial institutions, and analyzes this contract from the Islamic point of view.